Migration Narratives Diverging Stories in Schools, Churches, and Civic Institutions - Wortham, Stanton (Bloomsbury Academic, 2020)
Migration Narratives presents an ethnographic study of an American town that recently became home to thousands of Mexican migrants, with the Mexican population rising from 125 in 1990 to slightly under 10,000 in 2016. Through interviews with residents, the book focuses on key educational, religious, and civic institutions that shape and are shaped by the realities of Mexican immigrants. Focusing on African American, Mexican, Irish and Italian communities, the authors describe how interethnic relations played a central role in newcomers' pathways and draw links between the town's earlier cycles of migration. The town represents similar communities across the USA and around the world that have received large numbers of immigrants in a short time. The purpose of the book is to document the complexities that migrants and hosts experience and to suggest ways in which policy-makers, researchers, educators and communities can respond intelligently to politically-motivated stories that oversimplify migration across the contemporary world. This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. It is funded by Boston College.